Hipolito Unanue as seen by Augusto Salazar Bondy: The organicist tradition of science in Peru - Ballón, José Carlos (2005)
There is a sort of consensus on ideas on Peru among historians in characterizing Unanue and the young people grouped around him in the journal Mercurio Peruano (1790–1795) as founders of Peru’s illustrious thinking. Notwithstanding, a meticulous textual investigation of Hipolito Unanue’s scientific work shows the presence of a paradigm of natural scientificity that operated with categories and perspectives notoriously divergent from the illustrated mechanicist tradition. With the same scientific spirit Unanue reflects the intercrossing of two paradigms in dispute since the XVII century: the physicalmathematical reasoning that opposes the historical-natural reasoning. I am going to sustain the hypothesis that Unanue’s epistemologic option was not a personal business but a historical characteristic prevalent in our scientific community. It denotes hegemony of the nature’s organicist paradigm and a methodology linked to the biological sciences. Today maybe such exam may help us to determine our weaknesses and comparative advantages in the task of developing a modern scientific culture in Peru. It is possible that the predominance of the organicist tradition in our national scientific community might have been a hard obstacle for the development of certain scientific disciplines where the mechanicist paradigm was fruitful (particularly in the physical sciences). But it is also true that the organicist paradigm represented a strong stimulus for the development of the so called biological sciences that have reached important development in Peru.